Prognostic biomarkers for cardiovascular injury in patients with COVID-19: a review - T. V. Kanaeva; N. A. Karoli (Сеченовский вестник)
Investigations into the causes of adverse outcomes of the novel coronavirus infection (COVID-19) have been ongoing since the beginning of the pandemic. There is evidence that coronavirus-induced cardiovascular injury is as important to a risk of adverse outcome as respiratory injury. Many studies have shown that concomitant cardiovascular disease aggravates the course of COVID-19. However, in some patients who did not have cardiovascular diseases before COVID-19, they are detected during hospitalization or after discharge from the hospital. The review examines data on the effect of serum biomarkers of cardiovascular disease determined during COVID-19 on the risk of adverse outcomes in the near and long-term follow-up periods. Among such biomarkers are considered: troponins, N-terminal pro B-type natriuretic peptide, creatine phosphokinase-MB, lactate dehydrogenase, myoglobin, growth stimulation expressed gene 2, pentraxin 3, angiotensin II, as well as D-dimer and homocysteine. Threshold values have been set for some of these biomarkers, which allow predicting the risk of an unfavorable outcome. At the same time, in most prognostic models, these markers are considered in association with cytokine storm indicators and other risk factors.